2019
DOI: 10.1186/s11658-019-0180-y
|View full text |Cite
|
Sign up to set email alerts
|

SOX2 promotes hypoxia-induced breast cancer cell migration by inducing NEDD9 expression and subsequent activation of Rac1/HIF-1α signaling

Abstract: Background: Hypoxia, a major condition associated with the tumor microenvironment, stimulates the migration of cancer cells. SOX2 is a powerful transcription factor that shows higher expression in several cancers, however, its role in hypoxia-induced breast cancer cell migration remains largely elusive. Methods: The human breast cancer cell lines MDA-MB-231 and MDA-MB-468 were cultured under hypoxic conditions. The cell migration rate was determined using the wound-healing and transwell assays. The protein lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 37 publications
2
19
0
Order By: Relevance
“…Recently, a SOX2 knockdown experiment shows that basal cell carcinoma migration is regulated by Akt signalling pathway [ 58 ]. In agreement, another recent study shows that hypoxia-induced breast cancer cell migration is regulated by SOX2 transcription factor [ 112 ].…”
Section: Deregulation Of Foxos In Cancer and Metastasissupporting
confidence: 87%
“…Recently, a SOX2 knockdown experiment shows that basal cell carcinoma migration is regulated by Akt signalling pathway [ 58 ]. In agreement, another recent study shows that hypoxia-induced breast cancer cell migration is regulated by SOX2 transcription factor [ 112 ].…”
Section: Deregulation Of Foxos In Cancer and Metastasissupporting
confidence: 87%
“…Since RAC1 is required for activation of HIF1α [ 36 38 ], and RAC1 is the best-characterized ubiquitylation target of the HACE1 E3 ligase [ 10 , 15 18 ], we wondered whether HACE1’s effects on HIF1α are mediated through RAC1. We found that RAC1 activation was higher under hypoxia than ambient conditions in HEK293 cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In gastric cancer, SOX2 enhances HIF-1α promoter activity to regulate glucose metabolism 61 . Previous work on the crucial role of SOX2 in breast cancer cell migration showed that SOX2 upregulation in hypoxic conditions facilitated NEDD9 transcription and subsequent activation of HIF-1α expression 62 . This evidence extends our knowledge with regard to the diverse roles of SOX2 and HIFs in cancers.…”
Section: Discussionmentioning
confidence: 95%